Role of Helicobacter pylori infection in cancer‐associated fibroblast‐induced epithelial‐mesenchymal transition in vitro. Issue 6 (23rd September 2018) - Krzysiek‐Maczka, Gracjana; Targosz, Aneta; Szczyrk, Urszula; Strzałka, Malgorzata; Sliwowski, Zbigniew; Brzozowski, Tomasz; Czyz, Jarosław; Ptak‐Belowska, Agata
Abstract: Background: Major human gastrointestinal pathogen Helicobacter pylori ( H. pylori ) colonizes the gastric mucosa causing inflammation and severe complications including cancer, but the involvement of fibroblasts in the pathogenesis of these disorders in H. pylori ‐infected stomach has been little studied. Normal stroma contains few fibroblasts, especially myofibroblasts. Their number rapidly increases in the reactive stroma surrounding inflammatory region and neoplastic tissue; however, the interaction between H. pylori and fibroblasts remains unknown. We determined the effect of coincubation of normal rat gastric fibroblasts with alive H. pylori (cagA+vacA+) and H. pylori (cagA−vacA−) strains on the differentiation of these fibroblasts into cells possessing characteristics of cancer‐associated fibroblasts (CAFs) able to induce epithelial‐mesenchymal transition (EMT) of normal rat gastric epithelial cells (RGM‐1). Materials and Methods: The panel of CAFs markers mRNA was analyzed in H. pylori (cagA+vacA+) ‐infected fibroblasts by RT‐PCR. After insert coculture of differentiated fibroblasts with RGM‐1 cells from 24 up to 48, 72, and 96 hours, the mRNA expression for EMT‐associated genes was analyzed by RT‐PCR. Results: The mRNA expression for CAFs markers was significantly increased after 72 hours of infection with H. pylori (cagA+vacA+) but not H. pylori (cagA−vacA−) strain. Following coculture with CAFs, RGM‐1 cells showed significant decrease in E‐cadherin mRNA, and the parallel increase in the expression of Twist and Snail transcription factors mRNA was observed along with the overexpression of mRNAs for TGFβR, HGFR, FGFR, N‐cadherin, vimentin, α‐SMA, VEGF, and integrin‐β1. Conclusion: Helicobacter pylori (cagA+vacA+) strain induces differentiation of normal fibroblasts into CAFs, likely to initiate the EMT process in RGM‐1 epithelial cell line.